Intercropping Allium tuberosum Rottler ex Sprengel (Amaryllidaceae) reduces Tetranychus urticae Koch (Acari: Tetranychidae) populations in strawberry - Hata, Fernando Teruhiko; Ventura, Maurício Ursi; Béga, Vinádio Lucas; de Paula, Maria Tereza; Camacho, Iara Muniz (EntomoBrasilis, 2017)
Abstract. The twospotted spider mite (TSSM), Tetranychus urticae Koch is one of the most important pests on greenhouses/high tunnels worldwide. We evaluated effects of Chinese chive grown under the wooden structure which supports the bags used of strawberry grown, in two high tunnels from November 2016 to January 2017. TSSM mobile forms and number of eggs were counted on strawberry leaves. Five plants were randomly chosen on each plot. TSSM populations on strawberry leaves were assessed with magnifying glass (10 ×). Reductions were observed on three of eight assessments on TSSM mobile forms. On one date was observed reductions on mean number of TSSM eggs. Cumulate mite days overall data of TSSM mobile forms from two high tunnels reveals a reduction with intercrop. On the other hand, number of eggs was not altered. Results suggest that Chinese chive intercropped can reduce TSSM populations on strawberry high tunnels. Efeito do cultivo consorciado de Allium tuberosum Rottlerex Sprengel(Amaryllidaceae) em populações de Tetranychus urticae Koch (Acari: Tetranychidae) em morangueiro Resumo. O ácaro-rajado, Tetranychus urticae Koch, é uma das mais importantes pragas em casas de vegetação no mundo. Foi avaliado o efeito do consórcio de cebolinha chinesa, cultivada sob as estruturas de madeira que suportam as sacolas para o cultivo de morangueiro (sistema suspenso), em duas casas de vegetação, entre novembro de 2016 e janeiro de 2017. Formas móveis e ovos de ácaros foram contabilizados em folhas de morangueiro. Para as avaliações, cinco plantas foram aleatoriamente selecionadas em cada parcela. Populações de ácaro-rajado em folhas de morangueiro foram avaliadas com lupa de bolso, com 10 x de aumento. Reduções foram observadas em três de oito avaliações de formas móveis de ácaro-rajado. Foram observadas reduções no número de ovos em uma avaliação. Tomando em consideração os dados de ácaros acumulados por dia, foi observado que o consórcio reduziu em 54% a população de ácaros. Por outro lado, o número de ovos não foi alterado.